Economic Study of Offshore Marginal Oil Field Development - D D Prasetyo, S Kartohardjono (International Journal of Advanced Science and Technology, 2020)
On the pass decade, development to find oil and gas sources seem an easy and not complicated, it was due to developed area had a high economic profile and determined risk level. But over the time, remaining reserves will have high level of difficulty, it would need high effort and special treatment to develop marginal field become an economical project. This paper will discussing on how to modelling development of offshore marginal oil field X as integrated solutions with source of gas from field Y for injection, lifting, make-up and fuel. First by set new design and operation philosophy starting from basic requirement, determining the parameters, assembling into a number of integrated options, continue with risk, technical and economic studies. Finally optimize the result with sensitivity parameters to be able to produce the most optimal and economic scenario. Spreadsheet use during analyzing for modelling input parameters, to optimize value of IRR, NPV, POT and to perform sensitivity analysis. The results of this optimization will provide a real picture for management as a guidance to take further direction. Finally, the project becomes economical to be carry out, give additional portfolio to Contractor, help to meet the needs of energy supply and contribute multiplier effect on the national economics.